Agency over a phantom limb and electromyographic activity on the stump depend on visuomotor synchrony : a case study - Imaizumi, Shu (2014)
Most patients, post-amputation, report the experience of a phantom limb. Some even sense voluntary movements when viewing a mirror image of the intact limb superimposed onto the phantom limb. While delayed visual feedback of an action is known to reduce a sense of agency, the effect of delayed visual feedback on phantom motor sensation (i.e., sense of controlling a phantom limb) has not been examined. Using a video-projection system, we examined the effect of delayed visual feedback on phantom motor sensation in an upper-limb amputee (male; left upper-limb amputation). He was instructed to view mirrored video images of his intact hand clasping and unclasping during a phantom limb movement. He then rated the intensity of the phantom motor sensation. Three types of hand movement images were presented as follows: synchronous, asynchronous with a 250-ms delay, and asynchronous with a 500-ms delay. Results showed that phantom motor sensation decreased when the image was delayed by 250 and 500 ms. However, when we instructed the patient to adjust the phase of phantom limb movement to that of the image with a 500-ms delay, phantom motor sensation increased. There was also a positive correlation between intensity of phantom motor sensation and electromyographic (EMG) activity on deltoids at the patient’s stump. These results suggest that phantom motor sensation and EMG activity on the stump depend on visuomotor synchrony and top-down effects.